ABOUT THE METHOD OF KNITTING DOUBLE-SIDED PLUSH JERSEY ON SINGLE LINE MACHINES. THE KNITTING METHOD OF DOUBLE-SIDED PLUSH KNITWEAR ON A SINGLE-KNITTING MACHINE (Conferencea, 2023)
The article provides information on the development of a new mechanism for the production of double-sided plush knitwear on a single-knitting machine.